PERNIKAHAN BEDA AGAMA DALAM TAFSIR IBNU KATSIR, TAFSIR AL MISBAH DAN PERSPEKTIF 4 MADZHAB - Fariha Bidayatu Salwa; Bashirotul Hidayah (PT. Hasba Edukasi Mandiri, 2026)
Marriage is a sacred, legal relationship between a man and a woman for a long time. And this wedding is the longest worship among other worship. A common belief is needed so that marriage can be worthy of worship. Nowadays there are many phenomena of interfaith marriages emerging, matters of marriage and religion cannot be separated from each other, because religion regulates matters regarding marriage. This research contains the views of Imam Ibnu Katsir, Quraish Shihab and imams of 4 schools of fiqh regarding interfaith marriages. The discussion in this research uses a library research approach. Library research is an in-depth process of collecting information from various sources in libraries, both physical and digital, to support certain research or studies. The results of this research are that it is permissible for Muslim men to marry women who are people of the book, but not Muslim women to non-Muslim men or people of the book. This is not only understood from the text of the verse which does not mention this, as the meaning is mentioned, but also from other verses and the practices of friends. Priority should be given to the women chosen for marriage who are Muslim women, but even if they are other than them, they may be people of the book provided they have good morals and maintain their honor.